CCAAT/Enhancer-Binding Proteins in Fibrosis: Complex Roles Beyond Conventional Understanding - Lexun Wang; Jiaojiao Feng; Yanyue Deng; Qianqian Yang; Quxing Wei; Dewei Ye; Xianglu Rong; Jiao Guo (Research, 2022)
CCAAT/enhancer-binding proteins (C/EBPs) are a family of at least six identified transcription factors that contain a highly conserved basic leucine zipper domain and interact selectively with duplex DNA to regulate target gene expression. C/EBPs play important roles in various physiological processes, and their abnormal function can lead to various diseases. Recently, accumulating evidence has demonstrated that aberrant C/EBP expression or activity is closely associated with the onset and progression of fibrosis in several organs and tissues. During fibrosis, various C/EBPs can exert distinct functions in the same organ, while the same C/EBP can exert distinct functions in different organs. Modulating C/EBP expression or activity could regulate various molecular processes to alleviate fibrosis in multiple organs; therefore, novel C/EBPs-based therapeutic methods for treating fibrosis have attracted considerable attention. In this review, we will explore the features of C/EBPs and their critical functions in fibrosis in order to highlight new avenues for the development of novel therapies targeting C/EBPs.